Social Entrepreneurship-Based Community Service Strategies to Increase Household Income - Sutrisno, Sutrisno (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
This study aims to analyze how social entrepreneurship-based community service strategies can contribute to increasing household income, particularly within low-income communities in Indonesia. The method employed is a literature review with a qualitative approach focused on enhancing scientific references related to community service. Data were collected from various credible sources, such as Google Scholar and reputable academic websites, covering the period from 1992 to 2025. Out of a total of 50 articles identified, only 32 were selected after a rigorous selection process based on relevance and academic validity. The findings indicate that a social entrepreneurship-based approach can increase household income through skills training, local product innovation, marketing digitalization, and multi-stakeholder collaboration involving universities, government institutions, and industry. Theories of Social Entrepreneurship, Community Empowerment, and the Sustainable Livelihoods Framework serve as the main conceptual foundations explaining the relationship between social empowerment and economic well-being. Social entrepreneurship-based community service represents an effective, innovative, and sustainable approach to building household economic independence while strengthening the role of higher education in socio-economic development.